Eosinophilic gastroenteritis in an immunosuppressed patient: a case report - Dhas, Clement J.; A., Murali; C., Yoganathan (International Journal of Advances in Medicine, 2018)
Eosinophilic gastroenteritis is a rare disease that is characterized by Eosinophil infiltration in one or multiple segments of the gastrointestinal tract. The etiology of this condition remains unknown. Eosinophilic gastroenteritis has heterogeneous clinical manifestations that depend upon the location and depth of infiltration in the gastrointestinal tract, and eosinophilia may or may not be present. This article reports a case of Eosinophilic Gastroenteritis in a 57 years old retroviral male patient, who presented with chronic diarrhea, bilateral pedal edema and eosinophilia. Ultimately, the diagnosis of eosinophilic gastroenteritis was clinched. The rare character of eosinophilic gastroenteritis and its varied clinical presentations often lead to delayed diagnosis and complications. Case reports may help to disseminate knowledge about the disease, thereby increasing the likelihood of early diagnosis and intervention to prevent complications.